Hybrid Work Sebagai Katalis: Mengoptimalkan Perilaku Inovatif Untuk Meningkatkan Kinerja Organisasi - Anisah, Anisah (Universitas Batanghari, 2024)
This study aims to examine the role of the hybrid work model as a catalyst in enhancing employees' innovative behavior to support organizational performance. Using an explanatory survey approach, this research involves 121 employees from companies implementing the hybrid work model. Data is analyzed using Structural Equation Modeling (SEM) with the assistance of AMOS software to illustrate the causal relationships between the variables studied. The expected results of this study provide an in-depth understanding of the contribution of the hybrid work model to employees' innovative behavior and its impact on overall organizational performance improvement.